Benthic habitat is an integral part of freshwater Mysis ecology - Stockwell, Jason D. (Freshw Biol, 2020)
1. Diel vertical migration (DVM) is common in aquatic organisms. The trade‐off between reduced predation risk in deeper, darker waters during the day and increased foraging opportunities closer to the surface at night is a leading hypothesis for DVM behaviour. 2. Diel vertical migration behaviour has dominated research and assessment frameworks for Mysis, an omnivorous mid‐trophic level macroinvertebrate that exhibits strong DVM between benthic and pelagic habitats and plays key roles in many deep lake ecosystems. However, some historical literature and more recent evidence indicate that mysids also remain on the bottom at night, counter to expectations of DVM. 3. We surveyed the freshwater Mysis literature using Web of Science (WoS; 1945–2019) to quantify the frequency of studies on demographics, diets, and feeding experiments that considered, assessed, or included Mysis that did not migrate vertically but remained in benthic habitats. We supplemented our WoS survey with literature searches for relevant papers published prior to 1945, journal articles and theses not listed in WoS, and additional references known to the authors but missing from WoS (e.g. only 47% of the papers used to evaluate in situ diets were identified by WoS). 4. Results from the survey suggest that relatively little attention has been paid to the benthic components of Mysis ecology. Moreover, the literature suggests that reliance on Mysis sampling protocols using pelagic gear at night provides an incomplete picture of Mysis populations and their role in ecosystem structure and function. 5. We summarise current knowledge of Mysis DVM and provide an expanded framework that more fully considers the role of benthic habitat. Acknowledging benthic habitat as an integral part of Mysis ecology will enable research to better understand the role of Mysis in food web processes.